Management Esports Guidelines to a Professional Sport for Female Players in Thailand - Phonsri , Nuttavut (Journal of Ecohumanism, 2025)
Background. Female gamers are integral to the establishment of Asia’s swiftly growing gaming market, and it’s crucial not to underestimate their impact. In Thailand, the changing landscape provides developers, teams, and sponsors with various opportunities to broaden their audience by employing marketing strategies designed specifically for female, with the goal of capturing their interest and involvement in the gaming community in Thailand. The ongoing changes in Thailand are positioned to drive the growth of E-sports in the region as well. Objective. The research had the objective to study the factors affecting the intention to play E-sports among female players in Thailand. Methods. The mix method was using both quantitative and qualitative to explore the factor affecting the intention to play E-sports among female players in Thailand. Result. The result found that the motivation factor was the most significant factor affecting the intention to play E-sports among female players in Thailand and the detail was express in many aspects of the motivation factor. Conclusion. Gender inequality still persists in various sports, including those that did not rely on physical strength. Meanwhile, the value of the E-sports industry was growing in accordance with the demographics, specifically targeting the Generation G audience and the female population. Therefore, promoting career pathways for female E-sports athletes will significantly contribute to the increasing value of the E-sports industry in Thailand.